Evaluasi Kritis dan Rekonstruksi Pemulihan Keadaan Semula dalam Hukum Acara Pidana Berbasis Pancasila - Andrea Hynan Poeloengan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to critically analyze the norm adequacy of restoring the original condition in Article 79 paragraph (1) of Law Number 20 of 2025 on the Criminal Procedure Code and to formulate a legal reconstruction model based on Pancasila values. The problem focuses on two main issues: the alternative formulation through the word “or” in Article 79 paragraph (1), which potentially selects partial restoration forms, and the operational implications of the seven-day execution time limit in Article 79 paragraph (3). To approach this issue, theoretical frameworks of Howard Zehr’s Restorative Justice, Jürgen Habermas’s Communicative Action, and Pancasila Legal Idea as a grand theory are utilized. Data were collected through library research on primary and secondary legal materials and analyzed prescriptively via grammatical, systematic, and teleological interpretations. This study concludes that Article 79 paragraph (1) is not purely materialistic as it explicitly includes forgiveness and medical or psychological costs, yet its disjunctive structure risks ignoring holistic victim needs assessment. The proposed reconstruction yields the God-Conscious Consensual Restorative Justice model, requiring cumulative-proportional restoration criteria, guaranteeing genuine voluntariness, and strengthening offender accountability and victim protection under Pancasila.